Pengaruh Sifat Machiavellian, Locus Of Control dan Kepribadian Hexaco Terhadap Dysfunctional Audit Behavior (Persepsi Mahasiswa Akuntansi Universitas Pendidikan Indonesia dan Universitas Padjadjaran Angkatan 2016 dan 2017) - Fachrul Satria Robfilard (Epistemik Press, 2021)
This study examines the dysfunctional behavior of auditing which is a conflicting behavior with ethics and morals, this is very important for students so that when they enter the world of work they can create a clean and fraud-free environment and conduct non-contradictory behavior with ethics and morals. This study aims to determine the effect of machiavellian traits, locus of control, and HEXACO's personality on Dysfunctional audit behavior in accounting students. This study uses a purposive sampling method with a survey approach. Data retrieval using a questionnaire distributed via google form to students who meet the criteria in this study are students who have contracted Auditing courses. Analysis tool on This research is multiple linear regression. The test results show that the Machiavellian trait has a positive effect on Dysfunctional audit behavior, Locus of control has a positive effect on dysfunctional audit behavior, while for HEXACO personality has a negative influence on dysfunctional audit behavior. This matter indicates that a person's personality can reduce indications for dysfunctional behavior audit.